Environmental Factors Associated with Larval Habitats of Anopheline Mosquitoes (Diptera: Culicidae) in Metema District, Northwestern Ethiopia - Esayas Aklilu; Mizan Kindu; Araya Gebresilassie; Solomon Yared; Habte Tekie; Meshesha Balkew (Tehran University of Medical Sciences, 2020)
Background: Malaria is one of the major public health concerns in Ethiopia. Control options available for the management of malaria, include case detection, personal protection and larval source management. Effective control of Anopheles larvae largely depends on understanding of the habitats of the vectors. The aims of this study were to identify the breeding habitats of mosquitoes and characterize the larval habitats in Gende Wuha Town in northwestern Ethiopia. Methods: Different aquatic habitats were sampled and characterized for anopheline larvae from November 2012 to June 2013. Results: In total, 2784 larvae of Anopheles mosquitoes were collected from various breeding habitats. Microscopic identification of the III and IV instars revealed the presence of seven Anopheles species. Of the Anopheles spp, Anopheles gambiae s.l. (80%) was the most predominant species in the study area. Spearman correlation coefficient results also determined that the density of An. gambiae s.l. increased significantly with habitat temperature (r= 0.346, p< 0.01). Significantly higher An. gambiae s.l. larvae were obtained in non-shaded habitats (z= -3.120, p< 0.05) when compared with shaded habitats. Conclusions: The current study demonstrated An. gambiae s.l., the principal malaria vector in the country, is the predominant species in the larval sampling habitats. It was also noted the importance of edge of stream as larva breeding habitats for this species during the dry season of the year. Therefore, attention should be given for this breeding habitat for control of the vector during dry season.